Antioxidant components of chincho (tagetes elliptica sm): vitamin c and flavonoids - Natividad Bardales, Ángel D. (2009)
The chincho (Tagetes elliptica Sm) is an aromatic grass of the mountain range of Peru, normally is used as culinary additive, apart from this curious property, in some cases it is used for therapeut i c aims, whi ch apparent l y demonstrates it possesses other properties. With the aim to extend the information on the functional properties of this vegetable, it was proposed to investigate the antioxidant components: vitamin C and flavonoids, therefore it was proposed the following aims: determine the content of vitamin C (for espectrofotometría), flavonoids 3-hidroxilo in aqueous extracts and etenólico (for espectrofotometría), and the content of catequinas in the leaves of chincho (for HPLC). The results were: Vitamin C is equal to 14,49 mg of ascorbic acid /100g of humid sample; Flavonoids 3-hidroxilo is equal 39,72 mg of galic acid/g of sample and Flavonoids in terms of catequinas is equal to 396,665 μg/ml of extract. In basis to the study, it was reached the conclusion that the Chincho, apart of its good culinary quality, it presents very low conditions to be considered like an antioxidant capacity or a vegetable with nutritional properties.